Securing food for all in Bangladesh - Ahmed, Akhter; Islam, Nurul; Mujeri, Mustafa K. (International Food Policy Research Institute, 2021)
Securing Food for All in Bangladesh presents an array of research that collectively address four broad issues: (1) agricultural technology adoption; (2) input use and agricultural productivity; (3) food security and output market; and (4) poverty, food security, and women’s empowerment. The fifteen chapters of the book address diverse aspects within these four themes.